Methods of auditing cash at the enterprise - Natalya Bondarenko (University Economic Bulletin, 2025)
The relevance of the topic was due to the fact that in the context of economic instability, cash audit is becoming a key tool for monitoring the effectiveness of enterprise financial resources management, given their high liquidity and complexity of accounting. The aim of the study was to summarise the theoretical foundations of cash audit and develop practical recommendations adapted to the realities of Ukrainian enterprises. The research methodology was based on a combination of theoretical analysis and practical observations using the methods of induction, deduction, generalisation and source analysis, which ensured the identification of the main problems in the field of cash audit at the enterprise and the development of effective approaches to their solution. The article comprehensively examined the purpose of cash audit, outlined the main tasks of the auditor and systemises information resources, which will facilitate a high-quality audit and provide the auditor with the knowledge necessary for effective planning, conducting the audit, minimising errors and preparing reliable audit reports. Particular attention was paid to the audit procedures used at different stages of the audit, which will allow the auditor to deeply understand their specifics and effectively use them to obtain objective and reliable audit evidence. The article presented approaches to the classification of audit control methods used in Ukraine, with special attention paid to documentary verification and calculation and analytical techniques as key elements of ensuring a high-quality audit of cash at Ukrainian enterprises. An improved methodology was proposed, which included not only a general audit plan and programme, but also a detailed test of the accounting and control system. This will allow the auditor not only to verify the correctness of the cash flows, but also to assess the effectiveness of the internal control system. To facilitate and improve the quality of the audit, special working documents have been developed to help systemise information and ensure its reliability. The results of the study can be used not only in the practical activities of auditors, but also in the educational process of higher education institutions.
Keywords: 330; audit; cash transactions; procedures; audit stages; general plan; programme; working document